Drying of Pinus caribaea var. hondurensis using microwave radiation - Luckert Froget, Simón E. (2022)
A methodology was developed for drying Pinus caribaea var. hondurensis, using a domestic microwave oven (HMO) consisting of radiation pulses and cooling periods and consumes 92% less energy and 58% less time. The physical and mechanical properties were measured in the dry condition of HMO, hygroscopic equilibrium (HE) and conventional drying, ρgreen: 1049 ± 74 kg/m3 (CH: 107 ± 18%), ρdryHMO: 555 ± 63 kg/m3, ρEH : 565 ± 51 kg/m3 (CH: 11.3 ± 0.8%), Vgreen: 58 ± 1 x 10-6 m3, VHMO: 51 ± 26 x 10-6 m3, and volumetric contraction: 11 ± 3%, which do not present significant differences with respect to conventional drying. The values ​​of compression parallel to the grain were: ELPHMO: 6 ± 2 x 106 kg/m2, MRHMO: 6 ± 2 x 106 kgm2 and MOEHMO: 4 ± 1 x 108 kg/m2, ELPEH: 3,0 ± 0.5 kg/m2, MREH: 3,5 ± 0.64 kg/m2 and MOEEH: 2,3 ± 0.6 kg/m2, and not show differences with respect to conventional drying. The only anatomical alteration observed was an increase in spiral cracks in the walls of the tracheids and does not seem to have an impact on the evaluated properties. It was concluded that microwave exposure does not alter the studied properties and is a reliable method for drying.